Микроэлементы и почвенные микроорганизмы - Бершова Ольга Ипполитовна (Наукова думка, 1967)
Экземпляры: КХ (20120918) / Инвентарный номер: 426254 / Цена: 0.86 / Сис.шифр: 631.4 / Авт.знак: Б 52 / ГРНТИ: 68 / ББК: 41